Potential Application of Learning Organization Principle in Zakat Institution in Malaysia - Aini, Ahmad; Norhaslinda, Nordin (Universiti Malaysia Pahang, 2015)
This paper explores the concepts and understandings of learning organization and examines the potential integration of the learning organization idea in Islamic organization, in this case, zakat institution. The study analyses four understanding of learning organization based on Ortenblad (2002) that are organizational learning, learning at work, learning climate and learning structure against the management practise at zakat institutions. The findings suggest that the idea of learning organization is in harmony with Islamic teaching in many ways. Empirical research on the practice of learning organization in Islamic organizations is needed to shed more lights on the subject. Theoretically, learning organization can be successfully implemented in Islamic organizations and zakat institution in particular can be a learning organizations.